2016
DOI: 10.1302/2058-5241.1.000054
|View full text |Cite
|
Sign up to set email alerts
|

Constrained liners, dual mobility or large diameter heads to avoid dislocation in THA

Abstract: Dislocation remains a common cause of failure after total hip arthroplasty. The limitations of existing approaches to address instability have led to the development of powerfull options: constrained liners, dual mobility and large heads. These implant-related options have proven to be very efficient, but have raised concerns.With constrained liners, restricted range of motion (ROM) is responsible for impingement leading to high likelihood of failure, depending on the design, with various failure modes.Improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
54
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 69 publications
1
54
1
Order By: Relevance
“…A larger head size implies a wider joint range of motion (Figure 4a versus Figure 4c) as stated by many authors; 23,24 however, according to Levinnek et al, there is no more benefit beyond 28 mm size 20 and this statement is here confirmed by the results concerning the internal rotation (compare the upper curves in Figure 4b and 4c).…”
Section: Discussionsupporting
confidence: 83%
“…A larger head size implies a wider joint range of motion (Figure 4a versus Figure 4c) as stated by many authors; 23,24 however, according to Levinnek et al, there is no more benefit beyond 28 mm size 20 and this statement is here confirmed by the results concerning the internal rotation (compare the upper curves in Figure 4b and 4c).…”
Section: Discussionsupporting
confidence: 83%
“…There was no difference in the 8-year survivorship between the two groups after excluding infections as the cause of revision. It has been stated previously that constrained implants may have an increased prevalence of impingement of the femoral neck on the cup, leading to liner damage, locking mechanism failure, dislocation, and loosening [10]. We did not find any evidence to support this assumption.…”
Section: Discussioncontrasting
confidence: 67%
“…Despite their advantages in terms of stability, constrained devices may result in a restricted range of motion and have a greater prevalence of impingement of the femoral neck on the cup. Impingement is responsible for high stress transmission to multiple interfaces, leading to liner damage, locking mechanism failure, dislocation, and loosening [10]. Therefore, the constrained acetabular device system is intended only for special situations where the patient has a high risk of dislocation because of a previous history of dislocation, severe joint laxity, palsy of the surrounding musculature, or abductor muscle deficiency.…”
mentioning
confidence: 99%
“… 12 The rationale for this is to reduce instability by increasing the jump distance without resorting to larger femoral heads. 13 A recent systematic review of revision THA using modern dual mobility bearings reported a dislocation rate of 2.2% at short-term follow-up, but only 1.2% needed re-revision, with the other 1% being stable after relocation. 14 …”
Section: Introductionmentioning
confidence: 99%